Residual inflammation in psoriatic arthritis patients in stable minimal disease activity - Macchioni, Pierluigi; Marchesoni, Antonio; Ciancio, Giovanni; Sandri, Gilda; Zabotti, Alen; Vukatana, Gentiana; Montaguti, Luca; Focherini, Mariacristina; Govoni, Marcello; Spinella, Amelia; Malavolta, Nazzarena; Zuliani, Francesca; et al. (Frontiers in Medicine, 2022)
Background In psoriatic arthritis (PsA), low disease activity as defined by the Minimal Disease Activity (MDA) index is considered a good treatment target. However, as MDA is based only on clinical findings, it might not capture pauci-symptomatic inflammation. Sensitive imaging such as ultrasound (US) might disclose residual inflammatory signs in PsA patients in MDA. Methods In this cross-sectional multicentre study, adult PsA patients on biologic treatment in MDA for at least 6 months were consecutively enrolled for a thorough clinical and US examination. Data collection included demographics, personal history, main patient’s reported outcomes, clinical and US findings of joints, tendon sheaths, tendons, bursae, and entheses involvement. All centres performed the US investigation in B-mode and Power Doppler (PD)-mode using the same US machine equipped with a 18-6 MHz and 13-5 MHz multifrequency linear probe. Statistical analysis included comparisons between groups and correlation tests. Results The 72 PsA patients enrolled in the study had a median duration of MDA of 12 (6-65) months. Overall, US examination revealed a low number of acute inflammatory lesions. However, 54% of patients had at least one PD signal in the examined tissues. A joint or enthesis positive PD signal was found in about 20% and 24% of patients, respectively. Synovial hypertrophy, enthesitis, and bursa enlargement were the most common lesions, detected in about 42%, 29% and 26% of patients, respectively. Conclusions PsA patients in a stable state of MDA may still have residual inflammation in peripheral articular structures detectable by US examination.